Feasibility Study Analysis of the Citizenship E-Module for Indonesian Language and Literature Education Students: Reviewed from Material and Media Aspects - Surahman, Harry; Setyowati, Endang (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
This study aims to determine the feasibility of the material and media aspects of the Citizenship E-Module for Indonesian Language and Literature Education Students. This study is a development study of the Citizenship E-Module for Indonesian Language and Literature Education Students. The development of the Citizenship E-Module for Indonesian Language and Literature Education Students refers to the 4D model developed by Thiagarajan et al. (1974) which consists of 4 stages, namely Define, Design, Development, and Disseminate, modified to suit this study. This textbook was tested for feasibility by material and media experts. The instrument used was an expert validation instrument. Based on the results of the study, it can be concluded that the Citizenship E-Module for Indonesian Language and Literature Education Students is declared suitable for use as a Citizenship E-Module for Indonesian Language and Literature Education Students by material and media experts.